DRAWSHEET-ASSISTED REPOSITIONING FOR LATERAL POSITIONING IN CRITICALLY ILL PATIENTS: A SYSTEMATIC REVIEW - Prawira, Ricky; Siregar, Yaumil Hafsani; Saputra, Dikki (Department of Nursing, Faculty of Medicine, Universitas Tanjungpura, 2026)
Background: Critically ill patients in intensive care units (ICUs) frequently experience prolonged immobility due to sedation, mechanical ventilation, and hemodynamic instability. Regular repositioning, particularly lateral positioning, is a key nursing intervention to prevent complications such as pressure injuries, impaired ventilation, and circulatory disturbances. Drawsheet-assisted repositioning is commonly used to facilitate safe patient handling; however, evidence regarding its effectiveness in ICU settings remains scattered. Objective: This systematic review aimed to evaluate current evidence regarding the effectiveness of drawsheet-assisted repositioning in facilitating lateral positioning among critically ill patients and its impact on repositioning efficiency, nurse workload, and patient safety outcomes. Methods: This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) guidelines. A comprehensive search was conducted in PubMed, Scopus, CINAHL, and ProQuest databases for studies published between January 2013 and December 2024. Search terms included combinations of “drawsheet,” “patient repositioning,” “lateral positioning,” “ICU,” and “critically ill.” Eligible studies included original research conducted in critical care settings that evaluated repositioning interventions using drawsheets or similar repositioning aids. Two independent reviewers performed study screening, data extraction, and methodological quality assessment using the Joanna Briggs Institute (JBI) critical appraisal tools. Results: Eleven studies met the inclusion criteria, including randomized controlled trials, quasi-experimental studies, and observational studies. Evidence suggests that drawsheet-assisted repositioning improves repositioning efficiency, enhances positioning accuracy, and reduces physical workload among nurses. Several studies also indicated potential contributions to pressure injury prevention through improved pressure redistribution and safer patient handling techniques. Conclusion: Drawsheet-assisted repositioning appears to be a practical and cost-effective strategy for supporting safe lateral positioning in critically ill patients. While current evidence suggests benefits for both patients and healthcare workers, further high-quality randomized trials are needed to establish its direct impact on clinical outcomes such as pressure injury incidence and ICU length of stay.